Tensile Strength Measurement for Foundry Sand Brick - Manasi V. Magdum; Dr. B.T. Salokhe; Prof. A.S. Mali (International Journal of Engineering and Management Research, 2018)
Tensile strength is an important concept in engineering, especially in the fields of material science, mechanical engineering and structural Engineering. The tensile strength of a material is the maximum amount of tensile stress that can be applied to it before it ceases to be elastic. If more force is applied the material will become plastic or even break. Passed the elastic limit, the material will not relax to its initial shape after the force is removed. See Hooke's Law and Modulus of elasticity. The tensile strength where the material becomes plastic is called yield tensile strength. This is the point where the deformation (strain) of the material is unrecovered, and the work produced by external forces is not stored as elastic energy but will lead to contraction, cracks and ultimately failure of the construction. Clearly, this is a remarkable point for the engineering properties of the material since here the construction may lose its loading capacity or undergo large deformations. On the stress-strain curve below this point is in between the elastic and the plastic region. The Ultimate Tensile Strength (UTS) of a material is the limit stress at which the material actually breaks, with sudden release of the stored elastic energy. Tensile strength is measured in units of force per unit area. In the SI system, the unit is Newton per square meter (N/m² or Pa - Pascal). The U.S customary unit is pounds per square inch (or PSI).